Mitochondrial Iron in Human Health and Disease - Cloonan, Suzanne (My University, 2019)
Mitochondria are an iconic distinguishing feature of eukaryotic cells. Mitochondria encompass an active organellar network that fuses, divides, and directs a myriad of vital biological functions, including energy metabolism, cell death regulation, and innate immune signaling in different tissues. Another crucial and often underappreciated function of these dynamic organelles is their central role in the metabolism of the most abundant and biologically versatile transition metals in mammalian cells, iron. In recent years, cellular and animal models of mitochondrial iron dysfunction have provided vital information in identifying new proteins that have elucidated the pathways involved in mitochondrial homeostasis and iron metabolism. Specific signatures of mitochondrial iron dysregulation that are associated with disease pathogenesis and/or progression are becoming increasingly important. Understanding the molecular mechanisms regulating mitochondrial iron pathways will help better define the role of this important metal in mitochondrial function and in human health and disease.
PUBLISHED
Keywords: Iron; Metabolism; Mitochondria